Climate Change 2014 - Impacts, Adaptation and Vulnerability: Part B: Regional Aspects : Working Group II Contribution to the IPCC Fifth Assessment Report. Volume 2, Regional Aspects - Intergovernmental Panel on Climate Change (Cambridge : Cambridge University Press, 2014)
This latest Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) will again form the standard reference for all those concerned with climate change and its consequences, including students, researchers and policy makers in environmental science, meteorology, climatology, biology, ecology, atmospheric chemistry and environmental policy.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Climatic changes